KEMAMPUAN KOSAKATA BAHASA JEPANG SISWA KELAS XII SMA NEGERI 4 PEKANBARU - Syariqoh, Fitria Nahdah; Widiati, Sri Wahyu; Yohani, Adisthi Martha (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2024)
Abstract: This study aims to determine the Japanese vocabulary skills of studentsin class XII of SMA Negeri 4 Pekanbaru. The data was obtained through a test conductedin one of the classes, namely class XII Humaniora 1. The test results showed that theaverage student score was in the low category, with an average score of 48. This findingindicates that students face difficulties in understanding and mastering basic Japanesevocabulary. These low scores indicate the existence of barriers in Japanese languagelearning which may stem from ineffective teaching methods, lack of student motivation,and limited learning resources. This study provides a preliminary picture of students'vocabulary ability as an evaluation material for further learning.Key Words: Japanese Vocabulary, Initial Ability, Vocabulary Test, Language Learning